COLLABORATIVE LEARNING THROUGH LESSON STUDY IN PMRI TRAINING FOR PRIMARY SCHOOL PRE-SERVICE TEACHER: THE SIMULATION OF POLYGON MATTER - Anna Fauziah; Ratu Ilma Indra Putri; Zulkardi Zulkardi (Jurnal Infinity, 2022)
Collaborative learning through lesson study has become one of the promising methods for improving the quality of education and improving teachers' quality, likewise with the PMRI approach. The combination of the two in the training for primary school pre-service teachers, specifically in the second simulation session, was observed and reported. This article aims to describe the collaboration process in the second session of the simulations about polygon learning at PMRI training for primary school pre-service teachers. A design research method of the development type was used in this study, only at the preliminary and development or prototyping phase. The research subjects are students of Primary School Pre-service Teachers of Sriwijaya University that consisted of eight students for the small group and 32 students for the field test. Data was collected through documentation, observation, and field notes. The result showed that there were good collaboration occurs between researcher-lecturer, lecturer-student, and between students at the plan-do-see-redesign stage of the lesson study.